Genetic variations of Toll-like receptor 9 predispose to systemic lupus erythematosus in Japanese population. Issue 7 (7th March 2007) - Tao, Kayoko; Fujii, Mutsuko; Tsukumo, Shin-ichi; Maekawa, Yoichi; Kishihara, Kenji; Kimoto, Yasutaka; Horiuchi, Takahiko; Hisaeda, Hajime; Akira, Shizuo; Kagami, Shoji; Yasutomo, Koji
Abstract : Background: Systemic lupus erythematosus (SLE) is characterised by dysregulation of autoreactive lymphocytes and antigen-presenting cells. Signalling through Toll-like receptor 9 (TLR9), a mediator of innate immune responses, has a role in activation of dendritic cells and autoreactive B cells. Objective: To investigate whether TLR9 polymorphisms are associated with an increased risk of SLE. Methods: DNA samples were obtained from 220 Japanese patients with SLE (with >4 American College of Rheumatology criteria for SLE) and 203 controls. The genetic variations of TLR9 were detected by PCR, followed by DNA sequencing. The promoter and enhancer activities of TLR9 were measured by luciferase reporter gene assay. The titres of anti-dsDNA antibodies in sera from control or TLR9-deficient mice were analysed by ELISA. Results: The G allele at position +1174 (located in intron 1 of TLR9) is closely associated with an increased risk of SLE (p = 0.029). Furthermore, patients with SLE tend to have C allele at position −1486 (p = 0.11). Both alleles down regulate TLR9 expression by reporter gene assay. TLR9-deficient mice under a C57BL/6 background possess higher titres of anti-dsDNA serum antibodies than control C57BL/6 mice. Conclusions: These results indicate that the presence of the G allele at position +1174 of TLR9 predisposes humans to an increased risk of SLE. It is speculated that TLR9 normally prevents the development of human SLE.